GROUP METHOD OF DEPRECIATION. - Lanham, James S. (The Accounting Review, 1947)
Abstract The article focuses on the group method of depreciation in accounting. The vast amount of accounting literature written on the subject of depreciation fails to include but a bare mention of the group method of depreciation. This is quite unfortunate in view of the wide use of the procedure. The writer became interested in the group method in early 1941 and found it to be widely used and accepted in the petroleum industry. The regulatory commissions seem to have pioneered in the study of the requirements of the group method of depreciation. In the early 1920's the Interstate Commerce Commission began a study of depreciation rates and methods. During this period the Commission discussed interest and straight-line methods of computing the depreciation charge and recommended the straight-line method because it thought that this method gave a more accurate statement of the profit and loss. The unit plan of depreciation seems to have been the preference of the Commission until about 1933, when it began specifying the use of the group plan.